Capacidades de linguagem mobilizadas no processo de leitura, por alunos do Ensino Fundamental, em textos jornalísticos sobre violência contra a mulher - Lima, Kesia Suyanne Pinheiro (2020)
This research happens in a Brazilian Basic Education classroom, fulfilled by the need to mobilize the language capabilities that researched students have difficulty, especially those related to the descriptor 11 (Establishing relationships between parts of a text, identifying repetitions or substitutions), based on the (nominal) cohesion mechanisms for the matriz de referência do SPAECE - Permanent System for the Evaluation of Basic Education in Ceará. We aim to invest in strategies that contribute to develop these language capabilities, from a qualitative research, ending in an intervention with a didactic sequence, based on the textual genre news, about the theme “violence against women”, about a perspective that language that is, at the same time, a condition for the construction of the social world and a way to find solutions to understand it. The theoretical framework that we used are the concepts of textual sequence proposed by Schneuwly and Dolz (2004) and language capacity by Dolz, Noverraz, Schneuwly (2004). We had like a model the perspective of Socio-discursive Interactionism (BRONCKART, 1999; 2006; 2007; 2008) and we review these concepts in the classroom. We organize the difficulties of the researched students from test activities, then developed language activities that we applied in a didactic sequence, aimed at verifying how we can contribute to a better mobilization of the students' capacities. We compared the results before and after the intervention, verifying that the students were able to rearrange their knowledge, so that we consider that the didactic sequence used in our research was effective in expanding the language abilities of the students analyzed.